Reducing air resistance acting on a ship by using interaction effects between the hull and accommodation. (1st January 2016) - Van He, Ngo; Mizutani, Keisuke; Ikeda, Yoshiho
Abstract: A study on saving energy as well as reducing resistance acting on a ship is important in maritime transportation. In this study, we present a study on reducing air resistance acting on a ship by using interaction effects between hull and accommodation. Firstly, we apply CFD tool to determine air resistance acting on the hull and the accommodation of the ship separately. Simulation result of air resistance then is compared with experimental data to validate the accuracy of the CFD. Secondly, air resistances acting on the ship with the accommodation as a whole system is computed. The results demonstrate that the interaction effects between the hull and the accommodation can be applied to reduce the total air resistance. Graphical abstract: Highlights: Accommodation located at fore give smallest air resistance. Reducing resistance is obtained by interaction effect between hull and accommodation. Accommodation built only flat plates located at fore can reduce air resistance.